POTRET PENGEMBANGAN PENDIDIKAN AGAMA ISLAM BAGI KAUM DHUAFA DI MUHAMMADIYAH - Edi Sugianto (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2022)
ABSTRACT Education is the right for all of citizens. It had been mandated by constitution, but the fact, in marginal society there are many orphans and poor people drop out from their school and be streets as their home. Muhammadiyah is a social-religious organization. It starts and plays an active role in the empowering of people and the nation, especially Islamic education for the poor people. By the principle of humanist-religious dakwah, Muhammadiyah develops many charitable efforts, one of which was an orphanage for orphans and poor people. This research aims to get data and information about the development of Islamic education for poor people at Muhammadiyah Orphanage, Rawamangun, East Jakarta. This research is field research. The researcher collected data by observation, interviews, and documentation. Then, analyzing data by using the Miles and Huberman model. Then making a summarize of data, presents it by narrative text, and making a conclusion and verifying it. This research concluded that, Muhammadiyah Rawamangun orphanage was very serious to develop Islamic education for orphans and poor people. It developed the programs by three methods: First, to establish an Islamic culture of life for 24 hours. Second, making a program for memorizing the holy Qur’an as a branding of orphanage. Third, giving a scholarship for orphanage children to explore Al-Islam and other sciences until university. Keyword: poor people, Islamic education, Muhammadiyah